2007
DOI: 10.1038/sj.ejcn.1602846
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BMI-based classification of adolescent overweight and obesity: choice of percentage body fat cutoffs exerts a large influence. The COMPASS study

Abstract: Objective: To determine the impact of commonly used body fat percentage (%BF) references when evaluating the sensitivity, specificity and misclassifications of body mass index (BMI) for obesity screening in adolescence. Subjects/Methods: A community-based sample of 3334 adolescents aged 15.270.6 years was studied. Weight, height and %BF were measured. Sensitivity, specificity, predictive values and type and extent of misclassifications were calculated. Truepositive subjects for overweight and obesity were defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 18 publications
0
29
1
1
Order By: Relevance
“…14,15 Two other studies on young Swedish males found a small but significantly increased risk for underweight also 16,17 (HR 1.14 in both studies), although only a trend in that direction could be detected in this study (HR 1.07, NS). This discrepancy may be explained by the lower statistical power, Figure 3 Incidence rates of disability pension illustrating the combined effects of body mass index (BMI) and smoking status (n ¼ 45 920).…”
Section: Discussioncontrasting
confidence: 51%
“…14,15 Two other studies on young Swedish males found a small but significantly increased risk for underweight also 16,17 (HR 1.14 in both studies), although only a trend in that direction could be detected in this study (HR 1.07, NS). This discrepancy may be explained by the lower statistical power, Figure 3 Incidence rates of disability pension illustrating the combined effects of body mass index (BMI) and smoking status (n ¼ 45 920).…”
Section: Discussioncontrasting
confidence: 51%
“…However, according to the %BF cut-offs recommended by McCarthy et al [19], 9 and 12% of the males were overfat and obese, respectively, and in females the corresponding percentages were 17.5 and 20.5%. This inconsistency between BMI and %BF has previously been documented [9,38] [39]. When using the WC cut-offs defined by the IDF, few were defined as having adverse levels, especially among the males.…”
Section: Discussionmentioning
confidence: 97%
“…12 However, as is true for the BMI, the adoption of international reference tables seems to increase the proportion of falsenegative cases. [19][20][21] This is the case with the non age-adjusted cutoffs proposed by Williams et al, 8 where the higher cutoffs generated lower prevalence of obesity and, hence, higher specificity (true-negative cases). As mentioned above, outcome underestimation generates lower sensitivity (true-positive cases), that is, the capacity to correctly identify the outcome presence; therefore, both Taylor et al's 9 and McCarthy et al's 10 cutoffs, which presented higher outcome prevalence, also demonstrated slightly better accuracy in identifying the presence of EBP.…”
Section: Discussionmentioning
confidence: 99%